Effect of Different diets on Growth and Survival of Angel Fish Pterophyllum Scalare (Lichtenstein) Fry - Neelakanteswar A (Department of Aquaculture, College of Fisheries, 1997)
The effect of different diets on the growth and survival of Angel fish, Pterophyllum sealare (Lichtenstein) larvae was studied. One day old free swimming hatchlings were used in the study for a period of 30 days. The different diets used were Artemia nauplii, Moina micrura, artificial diet, Artemia nauplii + Moina micrura and Artemia nauplii + artificial diet, with four replicates for each treatment. The experiment was repeated twice in order to determine the consistency of the result. The results showed that the growth of larvae, in terms of gain in length and weight and specific growth rate, was maximum with the mixed diet of live foods. The differences in growth between artificial diet and mixed diet of Artemia nauplii + artificial diet were not consistent. No significant difference was found in the survival rate of larvae fed different diets. O:N ratios showed that the nutritional state of the larvae fed artificial diet was more or less similar to that fed mixed diet of Artemia nauplii + artificial diet, which in turn was comparable with that fed live foods. Thus, the artificial diet has been found to be an effective replacement diet in the larval rearing of Angel fish.